Connecting the Quality of Life Theory to Health, Well-being and Education : The Selected Works of Alex C. Michalos - Michalos, Alex C. (Springer International Publishing : Imprint: Springer, 2017)
This volume connects aspects of personal health, overall well-being, and education to quality of life. It includes discussions of Galen's and Harvey's views of the movement of blood in human bodies, and differences in the research traditions of social indicators research and health-related quality of life research. It examines determinants of health and quality of life in a variety of populations, including the residents of the Bella Coola Valley of British Columbia, aboriginal residential school survivors in Canada, and diabetics versus non-diabetics. It describes relations between health survey and patients' medical chart reviews, the health and quality of life of older people, and the difference between good health and a good life. Other topics explored are student quality of life, comparisons of the quality of life of students, aboriginal and unemployed people, the impact of education on happiness and well-being, and liberal education. In addition, the volume presents Einstein's views of ethics and science, and unacknowledged authorship in scholarly publications. The final chapter gives a historical review of quality of life research in Canada over the past fifty years.
Keywords: Social sciences.; Medical research.; Quality of life.; Positive psychology.; elektronické knihy; electronic books